Pengaruh Audit Operasional Dan Sistem Pengendalian Manajemen Terhadap Kinerja Karyawan - Yunita Althin Natanael (Jurnal Riset AKuntansi dan Bisnis, 2021)
The expected objectives of this study are: To determine and analyze the effect of operational audit on the performance of employees of PT. Tenggerraja Jaya Teknik. To determine the effect of management control on the performance of employees of PT. Tenggerraja Jaya Teknik. To determine the effect of operational audit and management control simultaneously on the performance of employees of PT. Tenggerraja Jaya Teknik. This type of research is associative with quantitative methods. This research uses documentation data. The author carried out the distribution of questionnaires aimed at employees of PT. Tenggerraja Jaya Teknik. The sample in this study were 50 respondents from employees of PT. Tenggerraja Jaya Teknik. The software used in this study uses the Statistical Package for Social Science (SPSS). There is a significant effect of work Operational Audit on Employee Performance at PT. Tenggerraja Jaya Teknik. There is a significant influence of Management Control System on Employee Performance at PT. Tenggerraja Jaya Teknik. There is a significant effect of work Operational Audit and Management Control System on Employee Performance at PT. Tenggerraja Jaya Teknik.